2015
DOI: 10.1166/jnn.2015.11418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare-Earth Gd Incorporation on the Characteristics of ZnO Thin Film

Abstract: The doping of oxide-based semiconductors with rare-earth ions may serve as an alternative to transition metal doping with the possibility of room-temperature ferromagnetism. Here, highly transparent thin films of ZnO doped with a rare-earth element, Gd, were prepared via a sol-gel-derived precursor. A series of Gd-doped ZnO films with different Gd concentrations (0 to 8 at.%) were deposited onto glass substrates. XRD analysis revealed that the FWHM of the diffraction peaks increased with the increase of Gd com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This evidence suggested that each domain comprises various aggregates with a very close alignment. For 100 °C ≤ T G ≤ 300 °C, the relatively uniform distribution of bright/dark regions, corresponding to a higher local concentration of positive/negative poles, revealed a long-range magnetic ordering. A different situation was observed at 400 °C, due to the above observed quasi-1D anisotropic morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence suggested that each domain comprises various aggregates with a very close alignment. For 100 °C ≤ T G ≤ 300 °C, the relatively uniform distribution of bright/dark regions, corresponding to a higher local concentration of positive/negative poles, revealed a long-range magnetic ordering. A different situation was observed at 400 °C, due to the above observed quasi-1D anisotropic morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The average crystallite sizes D were estimated from the patterns presented in Figure 2a by using the Scherrer formula: [8][9][10][11][12][13][14]…”
Section: S3mentioning
confidence: 99%
“…The alteration of the structural, optical, and electrical characteristics of ZnO with a suitable dopant may be a practical and efficient method for enhancing device performance. In recent years, rare-earth elements (REEs), including Gd [ 5 , 6 ], Eu [ 7 ], Tb [ 8 ], Ce [ 9 ], Sm [ 10 ], Dy [ 11 ], and Nd [ 12 ], have been reported as dopants of ZnO, in order to create new types of diluted magnetic semiconductors (DMSs). This is because they can significantly improve the conductivity, luminosity, and magnetic properties, with the long lifetime of excited state and multiple valence electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the most promising dopant is gadolinium (Gd), which categorized into rare-earth elements that have good properties of high magnetic moment and produce stronger ferromagnetism at room temperature [3]. These combination of both elements making ZnO as good material for potential applications such as spintronics, magneto-electronic, and magneto-optical devices [4] [5]. Since spintronics are correlated with both manipulation and control on the spin of electron, thus enhancing the magnetic properties is very crucial to produce high degree polarization and long spin lifetimes [6].…”
Section: Introductionmentioning
confidence: 99%